Curbing Corruption In Nigeria: Prayers Or Behaviour Change? - Dauda, Muritala (Journal of Techno-Social, 2025)
It is a known fact that Corruption has done numerous havocs to all sectors of our country, and at the same time Nigerian government has made series of efforts to combat this terrible menace. This effort has led to the creation of anti-corruption agencies and other anti-fraud mechanisms to address these nefarious activities in the country. However, in-spite of all strategies introduced by government to fight corruption in the society, the believes that corruption as a cankerworm is not a disease caused by man needs to be clearly addressed. Rather than employing spiritual means and prayer sessions as an assured way to tackle corruption monster that has eaten deep into our fabric, this study seeks to justify the extent to what prayers can do, as well as impact of positive change of attitude and behaviour of people in curbing corrupt practices in the society. This research is a qualitative study that adopts force-field analysis to juxtapose in between prayers and attitudinal change as one of the preventive measures to combat corrupt behaviour in Nigeria. The paper recommends that rather than attributing human cause to nature on corruption matter, by expecting prayers to address all man-made problems, there are numerous measures or actions that man can take to correct many imbalances in the society through sanctions, enforcement of rule of law and policies, and above all positive behaviour change, without necessarily involving nature in what seems not to be concerned with.